Racial Identity and Student Satisfaction: Analyzing Black College-Student Experiences Through Social Media Expression - Kameron Drumright (The Young Researcher)
This paper explores how Black college students express their positive or negative experiences, opinions, and perspectives relating to racial/ethnic identity at their racialized learning institutions—either Historically Black College/University or Predominantly White Institution. Codes were identified from posts (n = 57) on X (formerly known as Twitter) by Black college students through keyword search based on issues prevalent in past scholarly literature as well as historical context—issues such as racial alienation, hostile interracial-interaction, and institutional discrimination. I analyzed these tweets primarily using a thematic analysis in order to triangulate the most commonly held views and opinions of these Black college students in conjunction with historical continuity and scholarly research. This paper identifies great psychological impacts of educational segregation and the concept of “triple consciousness”—an awareness of perception by institutions, by fellow Black peers, and self-reflection on how educational choices affect identity—expanded from W.E.B. DuBois’ theory of racial authenticity, among other findings. These findings suggest consistent patterns and differences in racial identity navigation across institutions. High rates of expressed external identity consciousness, persistent alienation, and institutional criticism show that, while legal segregation has long since ended, its psychological legacy continues to shape Black educational experiences today.